Evaluating Supply Chain Management Using the Fuzzy Analytic Hierarchy Process Technique - ALI Karbalaei Ebrahim; Davood Darvishi Selokolayi; Abbas Ahmadi (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: Environmental systems and supply chain management are complementary, and their implementation not only improves the environment within the country but also increases the sustainability and environmental performance of the global supply chain. The present study evaluates the supply chain management in the pharmaceutical system of selected public hospitals in Mazandaran province.Methodology: Experts completed the designed questionnaire to rank the factors affecting the evaluation of supply chain management in the pharmaceutical system. After collecting the data, they were analyzed using the fuzzy analytic hierarchy process. Various factors and models were identified by studying the research background. The conceptual model of the research was presented by experts in four categories of main criteria and 16 sub-criteria. These factors include managerial and employee, economic, organizational, and cultural factors.Findings: The results showed that economic factors weighing 0.266 are the most important regarding experts and have the first rank, followed by managerial and employee factors, organizational factors, and cultural factors. Also, among the sub-criteria, the factors of adopting a business strategy commensurate with environmental goals with a weight of 0.0936, first place, designing a competitive business plan for optimal price and quality with a weight of 0.0878, second place, and modelling the trade policies of leading countries with a weight of 0.0846, third place. Originality/Value: Given the importance of factor-related criteria in implementing supply chain management, this article examines the factors that affect managers to help find a suitable model for their future investment plans.